PENGARUH BAHASA BOOKLET PADA PENINGKATAN PENGETAHUAN PETERNAK SAPI PERAH TENTANG INSEMINASI BUATAN DI KELURAHAN NONGKOSAWIT, KECAMATAN GUNUNGPATI, KOTA SEMARANG - Sriroso Satmoko; Harini Tri Astuti (Jurnal Penyuluhan, 2006)
A research concerning the effect of booklet’s language on the dairy farmers knowledge gain regarding artificial insemination had been accomplished in Nongkosawit Village, Gunung Pati District, City of Semarang on April 3 to June 3, 2004. The objective of the research was to determine whether such an extension booklet language created an effect on the dairy farmers’ knowledge regarding artificial insemination. Fourty dairy farmers were selected purposively for this research. They were divided into two groups, with 20 members each. The first group was exposed to the first version of the booklet written Javanese, and the second group was exposed to the second version of the booklet written in bahasa Indonesia. One-way analysis of variance was used to analyze the data collected. The results pointed out that the effect of the booklets’ languages on the dairy farmers’ knowledge gains about artificial insemination was not significant at alpha equal to 0.05.